Fiscal and Monetary Policies in Nigeria: Key Aspects, Performance, and Policy Options (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
This paper reviews key aspects of Nigeria’s fiscal and monetary policies with the aim of examining the performance of the policies. The paper provides a synthesis of key facts and draws policy conclusions which include the following: (i) fiscal policies such as the oil-price-based fiscal rule introduced in 2004 have increased fiscal discipline and reduced fiscal deficit in Nigeria, hence the policies should be maintained; and (ii) compared to the period of direct or controlled monetary policy approach, monetary policy has performed better in Nigeria under the market-based approach introduced in 1993, therefore the latter approach should be maintained.